2018
DOI: 10.1515/sjpain-2017-0159
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic differences in posterior insula in patients with chronic temporomandibular pain

Abstract: Abstract Background and aims Chronic pain including temporomandibular disorder (TMD) pain involves a complex interplay between peripheral and central sensitization, endogenous modulatory pathways, cortical processing and integration and numerous psychological, behavioral and social factors. The aim of this study was to compare spectroscopic patterns of N-Acetyl-aspartate (NAA), total creatine (tC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…Several studies have indicated that TMD pain conditions are associated with changes in brain Metabolism. 101 In these studies, MRS imaging was used to assess neurochemical metabolites. It includes are N-acetyl aspartate (NAA), choline (Cho), and total creatine (tCr) as well as other metabolites such as glutamate (Glu), glutamine (Gln), and myo-insitol.…”
Section: Role Of Neuroimaging Markers In Tmd Painmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have indicated that TMD pain conditions are associated with changes in brain Metabolism. 101 In these studies, MRS imaging was used to assess neurochemical metabolites. It includes are N-acetyl aspartate (NAA), choline (Cho), and total creatine (tCr) as well as other metabolites such as glutamate (Glu), glutamine (Gln), and myo-insitol.…”
Section: Role Of Neuroimaging Markers In Tmd Painmentioning
confidence: 99%
“…It includes are N-acetyl aspartate (NAA), choline (Cho), and total creatine (tCr) as well as other metabolites such as glutamate (Glu), glutamine (Gln), and myo-insitol. 101 According to the previous literature NAA is a biomarker of neuronal health and axonal numbers, while Cho is associated with in-creased cell numbers, membrane synthesis, or membrane breakdown. tCr is considered an important marker of cell energy and cell metabolism.…”
Section: Role Of Neuroimaging Markers In Tmd Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise in relation to oro‐‐facial sensorimotor functions, the failure of patients to adapt to changes in the oral cavity, or the development of a chronic sensorimotor condition, may reflect oro‐facial malplasticity. For instance, brain‐imaging studies in humans have shown that temporomandibular disorders (TMD) or bruxism may be associated with structural and functional changes that occur in several brain regions involved in oro‐facial sensorimotor functions and that have been considered to reflect malplasticity; the CNS regions affected include the oro‐facial sensorimotor area and the supplementary motor area.…”
Section: Regulation Of Oro‐facial Sensorimotor Functionsmentioning
confidence: 99%
“…104 A more recent MRS study found increased total creatine in the posterior insula of patients with TMD and, furthermore, that increased choline and glutamate concentrations in the posterior insular cortex were correlated with clinical characteristics of TMD pain, including generalized pain. 105 Because MRI is a standard diagnostic tool in TN and is critical to evaluation for surgical treatments of TN, almost all patients with TN undergo neuroimaging. However, research MRIs often use specialized protocols and postprocessing techniques not typically used in clinical practice.…”
Section: Neuroradiological Biomarkersmentioning
confidence: 99%